2016
DOI: 10.1007/s11999-015-4393-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Tourniquet Use in TKA Affect Recovery of Lower Extremity Strength and Function? A Randomized Trial

Abstract: Background Tourniquet use during total knee arthroplasty (TKA) improves visibility and reduces intraoperative blood loss. However, tourniquet use may also have a negative impact on early recovery of muscle strength and lower extremity function after TKA. Questions/purposes The purpose of this study was (1) to determine whether tourniquet use affects recovery of quadriceps strength (primary outcome) during the first 3 postoperative months; and (2) to examine the effects of tourniquet application on secondary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(163 citation statements)
references
References 61 publications
(109 reference statements)
3
148
1
4
Order By: Relevance
“…In a prospective randomized study of 28 patients undergoing same-day bilateral TKA where tourniquet was used throughout the procedure on one limb and not on the contralateral, Dennis et al found lower post-operative quadriceps strength on the limb with the tourniquet that persisted at 3 months after surgery [6]. A recent study by Huang et al, comparing 3 different tourniquet application strategies using a "mini-midvastus" approach, found that serum inflammatory and muscle injury markers were lowest in the group where tourniquet was used only for cementation and not for the entire procedure [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective randomized study of 28 patients undergoing same-day bilateral TKA where tourniquet was used throughout the procedure on one limb and not on the contralateral, Dennis et al found lower post-operative quadriceps strength on the limb with the tourniquet that persisted at 3 months after surgery [6]. A recent study by Huang et al, comparing 3 different tourniquet application strategies using a "mini-midvastus" approach, found that serum inflammatory and muscle injury markers were lowest in the group where tourniquet was used only for cementation and not for the entire procedure [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, tourniquet usage may be a risk factor for postoperative thromboembolism [2,3], and other wound complications related to tissue hypoxia and reperfusion injury [4,5]. In addition, a recent study found that tourniquet usage may result in diminished quadriceps function during the first 3 months after surgery [6]. Two recent meta-analyses of the available randomized controlled trials (RCTs) on tourniquet usage both concluded that the available evidence supports the assertion that TKA with a tourniquet results in a significant decrease in intraoperative blood loss and transfusion rate, albeit with a slightly higher rate of minor wound complications [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that tourniquet use reduces ROM of joints through inflicting microscopic injuries to muscles, affecting cellular viability, and increasing postoperative pain and edema [16]. Dennis et al [35] also assessed the effects of tourniquet use on the function of lower extremities after knee arthroplasty and found that quadriceps strength in their no-tourniquet group was significantly higher than the tourniquet group. They observed this difference even three months after the surgery [36].…”
Section: Archives Of Medicine Issn 1989-5216mentioning
confidence: 99%
“…This is presumed to be due to the lack of ischaemic injury to the limb as well as the crush injury to the musculature. [19][20][21] There is also recent evidence that when a tourniquet is not used the quadriceps musculature maintains a greater degree of strength, and the knee has a better range of movement. [20][21][22] These factors can all improve patient recovery.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] There is also recent evidence that when a tourniquet is not used the quadriceps musculature maintains a greater degree of strength, and the knee has a better range of movement. [20][21][22] These factors can all improve patient recovery. 22,23 The above findings and modern surgical and anaesthetic techniques have resulted in a trend to reduce the tourniquet time or even perform the surgery without a tourniquet.…”
Section: Introductionmentioning
confidence: 99%